Zur Validität der Eppendorfer Stimmungs-Antriebs-Skala (ESTA III) = On the validity of the Eppendorfer mood and drive scale (ESTA III) - Richter, Paul; Schmitt, Wolfram (European archives of psychiatry and clinical neuroscience, 1985)
The paper examines the validity of the Eppendorfer Mood and Drive Scale (ESTA III). ESTA III is a self-rating instrument for evaluating the effect of therapy and for studying the course of affective psychoses. Empirical research on the validity of the scale has been carried out solely by the author of the test. Subsequent to a critical review of hitherto existing research on the validity of the instrument, our own validity studies are discussed. Our studies cast doubt on the concurrent validity of the instrument (comparison with the adjective check list / EWL-K). Analysis of our own data and Reanalysis of the data published by the author of ESTA III do not support the construct validity of the instrument.
Gesehen am 29.01.2021